Dampak Covid-19 Terhadap Implementasi Pembelajaran Daring pada Pendidik Madrasah Ibtidaiyah - Agnes Setyoningsih; Tuti Marlina (Moderasi : Journal of Islamic Studies, 2021)
Covid-19 has had many impacts on social life, one of which is in the education sector. Based on regulations that have been inaugurated by the government, teaching and learning activities are carried out online or in a network (online). Online learning is a learning activity whose interactions are carried out face-to-face through the internet using learning devices such as mobile phones. This study aims to explain the impact of Covid-19 on educators at MI Al Fithrah Surabaya and the teacher's efforts in implementing online learning. This research uses descriptive qualitative research. Descriptive research is research that functions to describe, describe or describe a phenomenon and facts that are investigated systematically, factually and accurately. Data collection in this study was through questionnaires and documentation. The data analysis technique in this study used data reduction, data compilation, and data summarization. The results of this study are online learning activities at MI Al Fithrah run well through careful learning preparation. Good learning planning can make learning activities run effectively. In addition to good learning planning, there are learning media to support student understanding and teacher professionalism is needed in educating students during the Covid-19 pandemic. Learning media such as video conferences are an alternative for teachers in monitoring students online regarding understanding the material. This is the teacher's benchmark in ensuring student focus in participating in online learning. Giving assignments is also a benchmark for teachers in knowing students' understanding in mastering a material.